Pemetaan Tingkat Kerawanan Banjir Berbasis Geospasial Di Kecamatan Bulawa - Delvi Saputri Djibu; Nurfaika Nurfaika; Daud Yusuf (-, 2026)
Flood is one of the most frequent hydrometeorological disasters in Indonesia and causes various impacts on the environment, infrastructure, and community livelihoods. Bulawa District, Bone Bolango Regency, is one of the areas with a high potential for flood hazards due to its topographic conditions, high rainfall intensity, and land-use changes. This study aims to map the spatial distribution of flood-prone areas in Bulawa District using a geospatial approach based on Geographic Information Systems (GIS). The data used in this study include rainfall, slope, river networks, land use, soil type, and elevation, which were processed using ArcGIS 10.8. The results indicate that flood hazard levels in Bulawa District are classified into three categories: low, moderate, and high. Areas with a high level of flood hazard are generally located in the southern part of the district, which is adjacent to coastal areas, while most other regions fall into the low-hazard category. Geospatial analysis revealed that rainfall, land use, and proximity to river networks are the main factors influencing flood hazard levels in the study area. The resulting flood hazard map can serve as a valuable reference for spatial planning, disaster mitigation, and regional development policy-making aimed at reducing flood risks in Bulawa District., and regional development policies aimed at reducing flood risk in Bulawa District.